A protocol for detecting the cytoplasm-exposed mitochondrial DNA - Hao Liu; Haixia Zhuang; Lin Zeng; Jianming Xie; Kailun Qiu; Du Feng (Mitochondrial Communications)
Mitochondria, being semi-autonomous organelles, possess a double membrane structure and harbor their own DNA, known as mtDNA. In situations of stress, mtDNA is released from the mitochondrial membrane and enters the cytoplasm. The mtDNA released into the cytoplasm plays a dual role in promoting both the initiation and escalation of intracellular reactive oxygen species (ROS), the activation of inflammatory pathways, and the death of cells. Consequently, the identification of intracytoplasmic mtDNA fragments holds immense significance in the realm of scientific investigation. In this paper, we delineate the experimental methodologies presently employed for quantifying intracytoplasmic mtDNA fragments.